Formulasi dan Karakteristik Bubur Kacang Merah (Phaseolus vulgaris L.) Instan dengan Pemanis Sukrosa, Isomalto-oligosakarida dan Fibercreme - Rhaesfaty Galih Putri; Priyanto Triwitono; Yustinus Marsono (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
This study aimed to characterize red kidney bean instant porridge formulation with sucrose (BKM S), isomalto-oligosaccharides (BKM IMO), and fibercreme (BKM FC) as sweeteners on sensory, chemical and physical properties. Isomalto-oligosaccharides and fibercreme are used as sucrose substitutes because they provide a sweet taste as well as high fiber that can provide health benefits. The result showed that IMO and FC as a sucrose replacement in red kidney bean instant porridge formulation did not affect the texture, instead of lowering the acceptance level. The formulations did not change rehydration time but reduced the viscosity, while the water holding capacity increased with IMO replacement but decreased in FC replacement. Besides, the formulations increased the amount of fiber and decreased calories.